1997
DOI: 10.5326/15473317-33-5-451
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic examination and treatment of osteochondritis dissecans of the femoral condyle of six dogs

Abstract: Arthroscopy was used to diagnose and treat osteochondritis dissecans (OCD) of the femoral condyle in six dogs. Bilateral lesions were seen in two dogs. The medial condyle was affected in five stifles, and the lateral condyle was affected in three stifles. Subchondral bone defects were identified on radiographs in six of eight affected stifles. Resolution of the lameness associated with the arthroscopic procedure occurred one-to-14 days (mean, three days) following arthroscopy. Lameness resolved completely in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 0 publications
1
30
0
5
Order By: Relevance
“…Surgical treatment may be performed by arthrotomy or arthroscopy. These techniques have met with limited success, although 1 report suggested that arthroscopic treatment resulted in good short‐term outcomes when subjectively compared with cases treated by arthrotomy 6 . Typically, a guarded‐to‐poor prognosis for high‐level, pain‐free function in the long term is communicated to clients before traditional treatment for stifle OC 1–4 .…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment may be performed by arthrotomy or arthroscopy. These techniques have met with limited success, although 1 report suggested that arthroscopic treatment resulted in good short‐term outcomes when subjectively compared with cases treated by arthrotomy 6 . Typically, a guarded‐to‐poor prognosis for high‐level, pain‐free function in the long term is communicated to clients before traditional treatment for stifle OC 1–4 .…”
Section: Introductionmentioning
confidence: 99%
“…The dog's lameness did not deteriorate postoperatively and was considered by the owners to have improved on preoperative status within 48 hours of surgery. Open stifl e surgery by lateral para-patellar arthrotomy is associated with more signifi cant postoperative discomfort than that seen in this patient (Bertrand andothers 1997, Hoelzler andothers 2004). Prospective, blinded, controlled trials would be required to assess whether there was a signifi cant decrease in postoperative morbidity using arthroscopy for management of patellar fractures by partial patellectomy.…”
Section: Discussionmentioning
confidence: 67%
“…However, open stifle surgery is invasive. Arthroscopic stifle surgery in small animal patients has been recommended to reduce rehabilitation times and decrease postoperative morbidity (Bertrand and others 1997, Hoelzler and others 2004, Bright 2010). In human orthopaedic surgery, the open approach to partial patellectomy has been criticised for being invasive and increasing postoperative rehabilitation times (Azarbod and others 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tears should be treated by ablation as described above (Bertrand et al, 1997). Prior to completion of the arthroscopy, the opposite femoral condyle and underlying meniscus should be checked for evidence of disease and treated appropriately, if required.…”
Section: Arthroscopically Assisted Surgery Of Ocd Of the Stifle Jointmentioning
confidence: 99%